2014
DOI: 10.5455/jva.20141208030829
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Toxic Effects of some Non-Steroidal Anti-Inflammatory Drugs (NASIDs) in Rats

Abstract: A comparative study was carried out on the toxic effects of some non-steroidal anti-inflammatory drugs [NSAIDs]; Paracetamol (acetominophen), Ibuprofen (Julifen) and Nimesulide (Usteinim) in rats. The parameters used in determining the level of toxicity were body weight, blood sugar level, haematological and biochemical changes. The rats were randomly divided into four groups (A, B, C and D) of six rats each. Group A served as the control, Group B was treated with Paracetamol at the dose of 14mg/kg, Group C wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Paracetamol, diclofenac and diazepam decreased significantly (p<0.01 and p<0.05) Hb at the mice of group B, C and F, respectively. On the 28 th day Hb was 10.18±0.22, 9.04±0.40, 11.12±0.28, 10.26±0.23, 10.10±0.40, 9.94±0.45 and 10.16±0.53, respectively in groups A, B, C, D, E, F and G. In confirmatory to the present findings, Ukwueze et al (2014) observed that prolonged use of paracetamol decreased Hb content significantly. This observation is also in agreement with the earlier reports on paracetamol of Oyedeji et al (2013) and Hossain et al (2003).…”
Section: Hemoglobin Content (Hb Gm %)supporting
confidence: 91%
“…Paracetamol, diclofenac and diazepam decreased significantly (p<0.01 and p<0.05) Hb at the mice of group B, C and F, respectively. On the 28 th day Hb was 10.18±0.22, 9.04±0.40, 11.12±0.28, 10.26±0.23, 10.10±0.40, 9.94±0.45 and 10.16±0.53, respectively in groups A, B, C, D, E, F and G. In confirmatory to the present findings, Ukwueze et al (2014) observed that prolonged use of paracetamol decreased Hb content significantly. This observation is also in agreement with the earlier reports on paracetamol of Oyedeji et al (2013) and Hossain et al (2003).…”
Section: Hemoglobin Content (Hb Gm %)supporting
confidence: 91%
“…The overdose of Nonsteroidal antiinflammatory drugs is associated with an increased toxicity. Also, this toxicity can lead to multiple complications, and may be result in death [4].…”
Section: Introductionmentioning
confidence: 99%
“…APAP toxicity is one of the main causes of poisoning world-wide. Several studies reported that excessive use or overdose of APAP can damage several organs (especially the liver: represents the site of formation of the toxic metabolites, and the kidney: represents the site of its clearance) and even death [2][3][4][5][6] Its toxicity is mediated by the activity of its reactive metabolite (N-acetylp-benzoquinoneimine, NAPQI), that generated via cytochrome P450 in liver.NAPQI is detoxified by the antioxidant effects of intracellular glutathione (GSH). Thus, an overdose of APAP cause depletion of cellular GSH [2].…”
Section: Introductionmentioning
confidence: 99%